Konstruksi Teologis tentang Tanggung Jawab Ekologis dalam Pembacaan Kejadian 1:26–28 - Dorkas Me, Desti; Suhadi; Purwonugroho, Daniel Pesah (Sekolah Tinggi Teologi Torsina Surakarta, 2025)
This research examines the theological construction of human role and responsibility in creation care based on an in-depth analysis of Genesis 1:26-28. The contemporary ecological crisis reveals a fundamental gap between the divine mandate given to humanity as stewards of creation and the reality of exploitative practices that damage the environment. Through a qualitative-descriptive approach that employs biblical exegesis, this study examines the theological significance of the human role as imago Dei within the context of creation. Textual analysis demonstrates that humanity is called not as absolute rulers, but as God's representatives (vice-regents) responsible for maintaining and preserving the integrity of creation. The theological-practical implications of this research include: the need for reformulating Christian environmental ethics that integrates ecological spirituality with concrete conservation actions, developing an ecological praxis that views environmental concern as an expression of love for God and neighbor, and forming faith communities committed to environmental justice for the well-being of all creation. This research contributes to the development of contextual eco-theology that bridges biblical insights with the challenges of the global ecological crisis. Abstrak Penelitian ini mengkaji konstruksi teologis tentang peran dan tanggung jawab manusia dalam pemeliharaan ciptaan berdasarkan analisis mendalam terhadap Kejadian 1:26–28. Krisis ekologis kontemporer menunjukkan adanya kesenjangan fundamental antara mandat ilahi yang diberikan kepada manusia sebagai penatalayan ciptaan dengan realitas praktik eksploitatif yang merusak lingkungan. Melalui pendekatan kualitatif-deskriptif dengan metode eksegesis biblika, penelitian ini menelusuri makna teologis dari peran manusia sebagai imago Dei dalam konteks penciptaan. Analisis tekstual menunjukkan bahwa manusia dipanggil bukan sebagai penguasa absolut, melainkan sebagai representasi Allah (vice-regent) yang bertanggung jawab memelihara dan menjaga integritas ciptaan. Implikasi teologis-praktis dari penelitian ini mencakup: perlunya reformulasi etika lingkungan Kristen yang mengintegrasikan spiritualitas ekologis dengan tindakan konkret pelestarian alam, pengembangan praksis ekologis yang memandang kepedulian lingkungan sebagai wujud kasih kepada Allah dan sesama, dan pembentukan komunitas iman yang berkomitmen pada keadilan ekologis untuk kesejahteraan seluruh ciptaan. Penelitian ini berkontribusi pada pengembangan eko-teologi kontekstual yang menjembatani wawasan biblika dengan tantangan krisis lingkungan global.